Acts 15 a model for a Spirit-led Synod process - Beirne, Margaret (2024)
Although Nicaea is commonly identified as "the first ecumenical Council", the narrative account of "the Council of Jerusalem" in Acts 15 makes a strong claim as its biblical precedent. In the Lukan narrative, the elders of the neophyte Christian communities came together to resolve a significant issue in the early Church. Guided by the Spirit, they worked through a process that sets a pattern for communal discernment in today's Church. Such an interpretation has been explored by several writers, but what I identify in this paper is the vital element of personal conversion on the part of the key participants. It is precisely this experience that enabled them to reach a peaceful resolution, and to receive joyful acceptance when they disseminated the decision to the nascent Christian communities. The paper concludes by outlining how this biblical narrative provides a fitting model for the Synod process.
Keywords: Council; Jerusalem; Communities; Spirit; Discernment; Synod